THE APPLICATION OF PROBLEM-BASED LEARNING (PBL) TO IMPROVE THE COMMUNICATION MATHEMATICS SKILLS OF STUDENTS GRADE VII - Putri Utami; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Mathematics lessons involving students are suspected as one of the causes of the lack of students' mathematical communication skills. The researcher aims to improve the skills of nonverbal communication mathematics students of class VII B State Junior High School 9 Yogyakarta (SMP Negeri 9 Yogyakarta) by implementing Problem Based Learning (PBL). The type of this research is Classroom Action Research (CAR). The subject of this research is the students of class VII B SMP Negeri 9 Yogyakarta academic year 2016/2017 with the number of students 34 people. At the same time, the object in this research is the whole process of applying Problem Based Learning (PBL). Data collection techniques are done through observation techniques, interviews, and documentation. The Instrument of data collection in the form of observation sheet, the result of the problem-solving of nonverbal communication skills of student mathematics, and the result of the interview. The subject of this research is a student of class VII B SMP Negeri 9 Yogyakarta academic year 2016/2017 with student number 34 people. At the same time, the object in this research is the whole process of applying Problem Based Learning (PBL). Data collection techniques are done through observation techniques, interviews, and documentation. The Instrument of data collection in the form of the observation sheet results in the completion of the problem of nonverbal communication skill exercise of student mathematics and interview result. The results of this research show that applying Problem Based Learning (PBL) can improve students' mathematical nonverbal communication skills. The improvement of students' mathematical nonverbal communication skills is derived from the average score of significant exercise improvement with the percentage of 65,32% in cycle I increased to a very high category with 86,90% percentage in cycle II.